Significant Outcomes in Case Law in the United States: Autism and IDEA in 2013, Transition Issues and Changes in Diagnostic Evaluation Criteria - Hill, Doris Adams; Taylor, Jonte (Journal of the American Academy of Special Education Professionals, 2017)
The authors examined 85 cases decided in 2013 where the facts centered on violations of the Individuals with Disabilities Education Act (IDEA) and the provision of a Free Appropriate Public Education (FAPE) for students with autism spectrum disorder (ASD). Trends in prevailing party by geographic location, court circuit, gender, and other specifics (including transition and changes in evaluation criteria) are explored and compared to earlier research. Suggestions for educators who provide services for students with ASD are provided as well as free evidence-based resources for professional development.